Peningkatan Aktivitas dan Prestasi Belajar Siswa SMP Negeri 9 Mataram pada Pembelajaran Materi Persamaan Garis Lurus dengan Menerapkan Model Discovery Learning - Ekky Irza Afriansyah; Nyoman Sridana; Hapipi Hapipi; Amrullah Amrullah (Griya Journal of Mathematics Education and Application, 2022)
This research aims to know about the increasing of students’ activities and achievement at grade VIII-F of SMP Negeri 9 Mataram academic year 2016/2017 in learning mathematics on straight-line equation topics with the implementation of Discovery Learning. Discovery Learning is a model for developing active student learning by finding themselves, investigating itself. The type of this research is classroom action research which was conducted in two cycles. Every cycle consists of planning, acting, observating, and reflecting. As each cycle consisting of two meetings. Data of students’ learning activities were obtained by observation and the students’ achievement data were obtained by a test at the end of each cycle. The result showed that the score of students’ activities on the first meeting of first cycle is 10,33, it is categorized quite active. While on the second meeting in the first cycle, the students’ activities score is 11,33 categorized high activity. Meanwhile, in the first meeting of second cycle, the students’ activities score is 13,34 categorized active. While on the second meeting in second cycle, the students’ activities score is 15,34 categorized very active. Based on that result, there is an increasing of students’ activities. Based on the analysis of evaluation results of students’ achievement, the average of the evaluation cycle I and II respectively is 82,84 and 88,00 with classical completeness of each cycle is 77,42% and 87,10%. By looking at the result obtained from cycle to another cycle, there is an increasing of students’ achievement. It can be conclude that the implementation of Discovery Learning model on straight-line equation topics can improve the students’ activities and achievement at grade VIII-F SMP Negeri 9 Mataram academic year 2016/2017.